2014
DOI: 10.1111/bld.12115
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the experts: a thematic analysis of parent's experiences of attending a therapeutic group for parents of children with learning disabilities and challenging behaviour

Abstract: Accessible summary• Parent groups can be helpful for parents of children with learning disabilities and behaviour problems.• We talked to parents who had attended the 'Confident Parenting' group to find out what they thought about it.• They told us that the group helped them in lots of ways and think it would help other parents like them too. SummaryThe Confident Parenting group is a therapeutic group for parents of children with learning disabilities and challenging behaviour, which is informed by the princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
15
0
2
Order By: Relevance
“…As described earlier, parents of children with intellectual disability and challenging behaviours frequently experience isolation and stigma (Griffith and Hastings, 2014; Thompson-Janes et al, 2014). Davies and Hall (2005) reported that parents with similar experiences can provide a model for positive coping with exceptional life circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described earlier, parents of children with intellectual disability and challenging behaviours frequently experience isolation and stigma (Griffith and Hastings, 2014; Thompson-Janes et al, 2014). Davies and Hall (2005) reported that parents with similar experiences can provide a model for positive coping with exceptional life circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Mead et al (2001: 6) define peer support as ‘a system of giving and receiving help founded on key principles of respect, shared responsibility, and mutual agreement of what is beneficial’. Peer support provides opportunities for families to obtain important information to inform decision-making and to build a network based on shared experiences (Daly et al, 2015; Davies and Hall, 2005; Hibbard et al, 2002; Solomon et al, 2001; Thompson-Janes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the research addressing family experiences of caring for a family member with a disability (see for example Cummins, 200;McConkey, 2005;McKenzie, Mayer, Whelan, McNall, Noone & Chaplin, 2017;Plant & Sanders, 2007;Storr, 2014;Thompson-Janes, Brice, McElroy, Abbott & Ball, 2014) a small subset of studies focuses on the experiences of families whose family member not only has intellectual disability but also challenging behaviour (see for example Hatton, Emerson, Kirby, Kotwal, Baines, Hutchinson, Dobson & Marks, 2010;Maes, Broekman, Došen, & Nauts, 2003;McGill, Tennyson, & Cooper, 2005;McGill, Papachristoforou, & Cooper, 2006). While a number of these studies identify the challenges and strains of these families, few show the detail of what family members do on a day-to-day basis to navigate their lives.…”
Section: Introductionmentioning
confidence: 99%
“…While this study is survey-based and focuses on people with autism, it is one of the few that begins to unpack the lives of families who live with and care for a member with challenging behaviour. Thompson-Janes, et al's (2014) study focused on parents' experiences of attending a therapeutic group for parents of children with learning disabilities and challenging behaviour. The study confirmed the findings of previous studies that group interventions are beneficial for the wellbeing of parents that fall into this category.…”
Section: Introductionmentioning
confidence: 99%